# Show that m-1 is a factor of m21 - 1 and m22 - 1

Put m = 1 in the first polynomial

m (1) = (1)21 – 1

= 1 – 1

= 0

So m-1 is the factor of m21 -1

Put m = 1 in the second polynomial

m (1) = (1)22 – 1

= 1 – 1

= 0

So m-1 is the factor of m22 -1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Champ Quiz | Polynomials29 mins  Methods to find zeroes of a Polynomial-246 mins  Remainder Theorem and Factor Theorem38 mins  Polynomials - Zero to Hero42 mins  Genius Quiz | Polynomials40 mins  Zeros and Degrees of a Polynomial41 mins  Introduction to Polynomials37 mins  Basic understanding of Polynomials37 mins  Quiz | Imp. Qs. on Algebraic Identities65 mins  QUiz on Previous year NTSE Questions45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 